(untitled) - Link, Howard A. (Honolulu, Hawaii, 1981)
A beautiful catalog of the exhibition shown at the Honolulu Academy of Arts and at Japan House Gallery, New York, in 1980-81. Fully illustrated with 50 color/black & white plates and 54 black & white figures. Printed in Japan.
Keywords: Art, Japanese,Nghệ thuật, Nhật Bản